Analisis Peranan Indonesia dalam Pemberian Bantuan Kemanusiaan Terhadap Etnis Rohingya di Era Jokowi - Nadia Tia Pramita; Zahidi, M. Syaprin (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2023)
The Rohingya ethnicity is one of the most sensitive ethnic groups in the world due to the violence that this ethnic group received in their own territory, and in the end, people from this ethnic group became stateless as a result of policies issued by the Myanmar government. Indonesia as one of the countries that upholds and elevates the value of Human Rights as well as being a leader in Southeast Asia, under Jokowi’s leadership, Indonesia is trying to show its participation in efforts to resolve this long-standing conflict with various efforts that prioritize humanity and peace such as by how to issue foreign policy with diplomacy, as well as the allocation of foreign aid with a focus on kindness that is mostly given to people of that ethnicity. This then raises the question of how the role given by the Indonesian government in the Jokowi era through the many humanitarian assistance provided by Indonesia to these ethnic groups. A qualitative descriptive method was chosen to explain this research using data collection techniques through literature review and using an approach to the concept of foreign policy and aid as well as the theory of aid allocation. The results of this study itself show that there was a significant contribution made by Indonesia in responding to the conflict.